The variability of the large genomic segment of Ťahyňa orthobunyavirus and an all-atom exploration of its anti-viral drug resistance - Kilian, Patrik; Valdes, James J; Lecina-Casas, Daniel; Chrudimský, Tomáš; Růžek, Daniel (Infection, genetics and evolution, 2013)
Ťahyňa virus (TAHV), a member of the Bunyaviridae family (California complex), is an important but neglected human mosquito-borne pathogen. The virus genome is composed of three segments, i.e., small (S), medium (M), and large (L). Previous studies on genetic variability of viruses within the California complex were focused on S and M segments, but the L segment remains relatively unstudied. To assess the genetic variation and the relation to virus phenotype we analyzed the L segment sequences of biologically diverse TAHV strains isolated in the Czech Republic and Slovakia. Phylogenetic analysis covering all available sequences of the L segment of TAHV clearly revealed two distinguished lineages, tentatively named as "European" and "Asian". The L segment strains within the European lineage are highly conserved (identity 99.3%), whilst Asian strains are more genetically diverse (identity 97%). Based on sequence comparison with other bunyaviruses, several non-synonymous nucleotide substitutions unique for TAHV in the L segment were identified. We also identified specific residue substitutions in the endonuclease domain of TAHV compared with the La Crosse virus. Since the endonuclease domain of the La Crosse virus has been resolved, we employed an all energy landscape algorithm to analyze the ligand migration of a viral polymerase inhibitor. This allowed us to demonstrate, at the atomic level, that this viral polymerase inhibitor randomly explored the specific residue substitutions in the endonuclease domain of the TAHV L segment.
Keywords: viry kalifornské encefalitidy; NSs; Bunyamwera virus; CAL; Genotype; Genome, Viral; endonuclease domain; PELE; virové proteiny; MP; DPBA; INKV; S; OROV; synonymous nucleotide substitution rate; maximum parsimony; AKAV; ts; open reading frame; LACV; Orthobunyavirus; virová léková rezistence; genotyp; OTU-like; BUNV; ML; Chatanga virus; genetická variace; fylogeneze; medium genomic segment; Phylogeny; sekvenční analýza DNA; d(N); N; M; ORF; Ťahyňa virus; Antiviral Agents; Drug Resistance, Viral; ovarian tumour-like; Encephalitis Virus, California; ED; Genetic variability; California complex; L; oropouche virus; RNA, Viral; Large genomic segment; sekvence nukleotidů; maximum likelihood; VF; protein energy landscape exploration; root mean square deviation; temperature-sensitive; Amino Acid Sequence; Viral Proteins; sekvence aminokyselin; genom virový; Base Sequence; Genetic Variation; CHATV; large genomic segment; Sequence Alignment; RNA virová; non-synonymous nucleotide substitution rate; small genomic segment; Sequence Analysis, DNA; antivirové látky; molekulární sekvence - údaje; valtice fever; RMSD; La Crosse virus; nucleocapsid protein; sekvenční seřazení; d(S); TAHV; lidé; nonstructural protein encoded by S segment; Humans; Inkoo virus; 2,4-dioxo-4-phenylbutanoic acid; Akabane virus; Molecular Sequence Data